Seducing an angel [compact disc, unabridged] - Balogh, Mary (Brilliance Audio ; Distributed by Recorded Books, 2009)
Cassandra, Lady Paget--banished, destitute, and labeled a murderess--arrives in Regency London and soon becomes the mistress of Stephen, Earl of Merton, a man of means who, despite his looks and easy charm, is no angel.